Implementasi Perilaku Pencarian Informasi Generasi Z Menggunakan Metode Krikelas di UPT Perpustakaan IAKN Tarutung - Ericson Marihot Hutapea (Jurnal Gema Pustakawan, 2026)
This study examines the implementation of Generation Z’s information-seeking behavior using the Krikelas model at the Library Unit (UPT) of the Tarutung State Christian Institute (IAKN). This descriptive research with a literature review approach adapts the Krikelas model, which focuses on how individuals recognize gaps in knowledge and seek solutions to specific problems. This model emphasizes triggers of information needs, starting from experiences or urgent needs, then proceeding through search actions (observation/personal data) until information is obtained. Generation Z, also known as the iGeneration, has grown up with gadgets and the internet as integral parts of their lives. As academic information management institutions, university libraries are required to understand these characteristics. The results show that Gen Z students at IAKN Tarutung have implemented the components of the Krikelas model to meet their information needs. However, a major challenge is identified where the active rate of registered members remains low (8.4%). This indicates that their information-seeking behavior is heavily dominated by preferences for external digital sources outside the library system, driven by efforts to minimize uncertainty rapidly.